THE SYSTEM OF THE UNIVERSITY EDUCATION QUALITY MANAGEMENT: THE EXPERIENCE OF THE EUROPEAN UNION - Batechko, Nina (Educological discourse, 2019)
The article deals with the current tendencies in the quality management of university education in the context of modern European practices. The evolution of the quality management system development in the European Union and the modern approaches to the quality problem of university education have been traced. The main tendencies in the development of the quality management system of university education in Ukraine have been determined, both at the state level and at the level of a separate institution of higher education. The expediency of implementing the best European practices for maintaining university education quality in Ukraine has been proved.